Ideas and Challenges for Securing Wireless Implantable Medical Devices: A Review - Guanglou Zheng; Shankaran, Rajan; Orgun, Mehmet A.; Li Qiao; Saleem, Kashif (IEEE sensors journal, 2017)
Implantable medical devices (IMDs) are normally used for monitoring and treating various medical conditions. These days, wireless modules have become an intrinsic part of many modern IMDs. So, doctors can use device programmers wirelessly to configure parameters in the IMDs. However, such a wireless technology exposes the IMDs to security attacks. In this paper, we analyze potential threats faced by the IMDs and discuss security solutions proposed in the existing literature to counter these threats. Securing an IMD involves three design tradeoffs that require a careful consideration. The first one is security versus accessibility in an emergency situation. We compare the IMD security schemes in the literature in terms of their merits and disadvantages. The second one is the tradeoff between the security schemes for supporting emergency access and those for supporting normal check-up access to the IMDs. This normal check-up access to the IMDs should avoid extra resource consumptions, which is different from the requirement in the emergency access. The third one is between the requirements of strong security and limited resources. The IMD, as a tiny wireless device used for medical purposes, has very limited resources when compared with a generic wireless sensor device/node. We analyze various schemes that aim to conserve the underlying resources of an IMD and also counter battery denial of service attacks from different perspectives. Based on the literature review, we analyze general concerns in the IMD security design from the system engineering point of view, and discuss possible future research directions.